Effort de conservation et Aires marines protégées : quatre illusions et un changement de perspective - Jean-Eudes Beuret; Anne Cadoret (VertigO)
In political and sometimes scientific arguments, the effort made for the conservation of marine biodiversity via Marine Protected Areas (MPA) is evaluated on the basis of classified areas, which implies that their status offers protection on the scale of their perimeter. More generally, MPAs are based on four pillars: a status, a perimeter, rules and a manager. An interdisciplinary international comparative analysis (geography and economy), based on 13 cases studied in highly differentiated geographical and societal contexts, leads us to return to four founding illusions according to which: a) the status marks the institutionalization of the MPA and offers protection; b) the perimeter of the MPA corresponds to the managed and protected surface; c) specific rules are necessary for conservation action and are designed to be enforced through sanctions; and d) the implementation of the territorial conservation policy implies a centrality, with a manager with or without authority. To these four illusions, described respectively as statutory, surface, normative and centralizing, correspond more complex realities illustrated by the case studies. Their analysis leads us to specify what MPAs are, to draw lessons from them for accompanying the processes of institutionalization of MPAs, and to offer new modalities and indicators for evaluating the effort made in favor of conservation.